Sherlock Bones and the natural history mystery - Treml, Renée (Etch, 2019)
Sherlock Bones, a frogmouth skeleton, and his trusty sidekick Watts, a stuffed parrot, live in the State Natural History Museum. When the museum's valuable Royal Blue Diamond is stolen, Sherlock and Watts set off to solve the mystery. They soon meet a friendly raccoon named Grace who keeps getting in the way. When they discover that the museum may have to close if the diamond isn't found, Sherlock and Watts must race against the clock to save their home.